2015
DOI: 10.1515/amm-2015-0227
|View full text |Cite
|
Sign up to set email alerts
|

The Prospects In Designing New Generation Of High Temperature Coatings In Automobile Engines

Abstract: The influence of the chromium layer with the thickness of 1 micrometer sputter-deposited on the X33CrNiMn23-8 and X50CrMnNiNbN21-9 steel surfaces on the oxidation behavior of these steels has been studied at 1173 K in air, using the microthermogravimetric technique. It has been found that coated materials show very good oxidation resistance under isothermal conditions, comparable with that of chromia formers, due to the formation of Cr 2 O 3 scales on their surfaces. It has been also demonstrated that the posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…It should be noted, however, that the beneficial influence of the discussed novel coatings on the oxidation behavior of valve steels has been investigated up to now only for two steels (X33CrNiMn23-8 and X50CrMnNiNbN21-9) under isothermal conditions. 18 Thus, the aim of this work was to study the oxidation behavior under both isothermal and thermal-shock conditions of four valve steels, X33CrNiMn23-8 (X33), X50CrMnNiNbN21-9 (X50), X53CrMnNiN20-8 (X53) and X55CrMnNiN20-8 (X55), covered with novel coatings, utilized at present for the production of engine valves; the obtained results are reported in the present paper.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted, however, that the beneficial influence of the discussed novel coatings on the oxidation behavior of valve steels has been investigated up to now only for two steels (X33CrNiMn23-8 and X50CrMnNiNbN21-9) under isothermal conditions. 18 Thus, the aim of this work was to study the oxidation behavior under both isothermal and thermal-shock conditions of four valve steels, X33CrNiMn23-8 (X33), X50CrMnNiNbN21-9 (X50), X53CrMnNiN20-8 (X53) and X55CrMnNiN20-8 (X55), covered with novel coatings, utilized at present for the production of engine valves; the obtained results are reported in the present paper.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that such coatings, in contrast to the rather thick and, thereby, expensive TBC corrosion-resistant coatings, contain a very small amount of chromium, which is, however, high enough to form a continuous layer of highly-protective Cr 2 O 3 oxide during the initial stage of oxidation. 18 The stability and further growth of this chromium oxide layer is a result of outward chromium diffusion from the protected material. Thus, the proposed novel coatings only play the role of the initiator for the formation of the Cr 2 O 3 layer, after which they disappear relatively fast.…”
Section: Introductionmentioning
confidence: 99%